Upaya Guru Dalam Meningkatkan Keterampilan Membaca Dan Menulis Permulaan Siswa Di Sekolah Dasar - Rivaldi Wiratama (Pendagogia: Jurnal Pendidikan Dasar, 2025)
Reading and writing are basic skills that must be mastered by students because they are the main key to learning other more complex things at a higher level. In the process, of course, there are still various problems that can hinder the development of students' reading and writing skills in elementary school. Through this scientific article, the researcher wants to explore further about teachers' efforts in improving and stimulating the development of students' reading and writing skills. This research was carried out at SDN 018 Sungai Perak. This article is written and presented with a qualitative method. The subjects of the research are teachers of grades I and II, the data needed in the research are obtained through observation, interviews, and documentation which are then processed and analyzed with Miles and Hubberman analysis techniques, namely data reduction, data presentation, and conclusion drawn. The results of the study showed that teachers' efforts in improving students' writing and reading skills were, improving children's motor skills through origami, using concrete examples, using spelling methods and game methods, and recognizing the level of ability of each student.